Lithium–Air Batteries: Air-Electrochemistry and Anode Stabilization - Chen, Kai; Yang, Dong-Yue; Huang, Gang; Zhang, Xin-Bo (Accounts of chemical research, 2021)
Conspectus It is a permanent issue for modern society to develop high-energy-density, low-cost, and safe batteries to promote technological innovation and revolutionize the human lifestyle. However, the current popular Li-ion batteries are approaching their ceiling in energy density, and thus other battery systems with more power need to be proposed and studied to guide this revolution. Lithium–air batteries are among the candidates for next-generation batteries because of their high energy density (3500 Wh/kg). The past 20 years have witnessed rapid developments of lithium–air batteries in electrochemistry and material engineering with scientists’ collaboration from all over the world. Despite these advances, the investigation on Li–air batteries is still in its infancy, and many bottleneck problems, including fundamental and application difficulties, are waiting to be resolved. For the electrolyte, it is prone to be attacked by intermediates (LiO2, O2 –, 1O2, O2 2–) and decomposed at high voltage, accompanying side reactions that will induce cathode passivation. For the lithium anode, it can be corroded severely by H2O and the side products, thus protection methods are urgently needed. As an integrated system, the realization of high-performance Li–air batteries requires the three components to be optimized simultaneously. In this Account, we are going to summarize our progress for optimizing Li–air batteries in the past decade, including air-electrochemistry and anode optimization. Air-electrochemistry involves the interactions among electrolytes, cathodes, and air, which is a complex issue to understand. The search for stable electrolytes is first introduced because at the early age of its development, the use of incompatible Li-ion battery electrolytes leads to some misunderstandings and troubles in the advances of Li–air batteries. After finding suitable electrolytes for Li–air batteries, the fundamental research in the reaction mechanism starts to boom, and the performance has achieved great improvement. Then, air electrode engineering is introduced to give a general design principle. Examples of carbon-based cathodes and all-metal cathodes are discussed. In addition, to understand the influence of air components on Li–air batteries, the electro-activity of N2 has been tested and the role of CO2 in Li–O2/CO2 has been refreshed. Following this, the strategies for anode optimization, including constructing artificial films, introducing hydrophobic polymer electrolytes, adding electrolyte additives, and designing alloy anodes, have been discussed. Finally, we advocate researchers in this field to conduct cell level optimizations and consider their application scenarios to promote the commercialization of Li–air batteries in the near future.